(untitled) (Fiep Bulletin - online, 2015)
This is the first volume of an Atlas of Physical Education with thousands of pictures of exercises together with their summarized description ; it is drawn up with great didactical care and is useful to teachers, trainers and performers. Its practical sense, systematization and elegant presentation, are to be praised very much.